2014
DOI: 10.2478/intag-2014-0027
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Long Storage and Soil Type on the Actual Denitrification and Denitrification Capacity to N2O Formation

Abstract: A b s t r a c t. The actual denitrification to N 2 O and denitrification capacity to N 2 O after flooding of different soil samples stored for over 25 years in air-dry conditions and fresh, air dried samples were compared in our study. Zero N 2 O release was observed from the stored soils but the fresh soil samples had very low actual denitrification to N 2 O. NO 3 -addition significantly increased the amount of N 2 O (denitrification capacity to N 2 O) released after flooding, which depended on the length of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Blake et al (2000) did not find any impact on total C during storage for air‐dried samples analysed first in 1959–1964, stored in a daylit room in lead‐sealed or waxed cork‐sealed glass bottles and re‐analysed in 1991. However, Włodarczyk et al (2014) found a storage effect on organic C concentration. Soil samples of different soil types were stored over 25 years in the Polish Bank of Soil under air‐dry conditions and compared with fresh soil samples taken from the same site in the year of analysis.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Blake et al (2000) did not find any impact on total C during storage for air‐dried samples analysed first in 1959–1964, stored in a daylit room in lead‐sealed or waxed cork‐sealed glass bottles and re‐analysed in 1991. However, Włodarczyk et al (2014) found a storage effect on organic C concentration. Soil samples of different soil types were stored over 25 years in the Polish Bank of Soil under air‐dry conditions and compared with fresh soil samples taken from the same site in the year of analysis.…”
Section: Discussionmentioning
confidence: 98%
“…Stored and fresh soil samples were air-dried, rewetted and subsequently analysed for SOC and microbial biomass activity and resulted in unexpected fractions of microbial biomass that survived storage (about 20% with 47 years and 10% with 80 years of storage; De Nobili et al, 2006). We remark that this increased SOC concentration in freshly taken soil samples for both studies (De Nobili et al, 2006;Włodarczyk et al, 2014) is likely to be related to land use changes and natural C turnover that took place over decades in the resampled soils, but not necessarily due to storage conditions. However, in the current study, soil moisture content was $1 Vol.…”
Section: Yearmentioning
confidence: 95%
“…1) suggests rapid oxygen uptake. In the anaerobic parts of the aggregates, following O 2 depletion, facultative anaerobes shift their metabolism and use NO 3 − as electron acceptors during denitrification (Włodarczyk et al 2014). The significant difference in the NH 4 + -N contents between the AP+ and AP− aggregates after 24 h of incubation may have been due to the intensive N assimilation associated with the rapid growth of microbial communities stimulated by apple pomace.…”
Section: Discussionmentioning
confidence: 99%
“…The most clustered results of the first measurement, (AD soils in Figure 3 ), indicate that the storage of a soil in AD conditions somehow equalizes the influence of the soil origin (type) on the volatile fingerprint. The microbial activity of AD soil is practically zero; however, the microorganisms can still be reactivated [ 50 ].…”
Section: Discussionmentioning
confidence: 99%